2014
DOI: 10.1177/1933719113518983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Endothelial Progenitor Cell (EPC)- or Mouse Vascular Endothelial Growth Factor-Derived Vessel Formation on the Survival of Vitrified/Warmed Mouse Ovarian Grafts

Abstract: The aim of this study was to evaluate the effectiveness of improving angiogenesis at graft sites on the survival of follicles in transplanted ovarian tissue. Matrigel containing 5 Â 10 5 of cord blood-derived endothelial progenitor cells (EPCs) or 200 ng of mouse vascular endothelial growth factor (VEGF) was injected subcutaneously into BALB/c-Nu mice. After 1 week, vitrified/ warmed ovaries from female B6D2F1 mice were subcutaneously transplanted into the injection sites. After 1, 2, and 4 weeks posttransplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…There is growing interest in EPCs due to their acclaimed role in maintenance of endothelial integrity and angiogenesis function as well as postnatal neovascularization in a variety of animal models. In previous studies, EPCs were suggested for applications into medical fields such as peripheral arterial disease (Fadini et al, ), coronary artery disease (Briguori et al, ), congestive heart failure (Valgimigli et al, ), lowering cholesterol (Vasa et al, ), anti‐diabetic medication (Wang et al, ), and early revascularization of ovaries (Cha et al, ). Although EPCs do not engraft into the vasculature, it is now considered that the primary role of the contribution to vascular functions by circulating EPCs is via the release of paracrine factors including VEGF, bFGF, and IL‐10 (Jujo, Ii, & Losordo, ; Yang, Wang, Qu, Duan, & Xu, ; Zhang, Malik, & Rehman, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in EPCs due to their acclaimed role in maintenance of endothelial integrity and angiogenesis function as well as postnatal neovascularization in a variety of animal models. In previous studies, EPCs were suggested for applications into medical fields such as peripheral arterial disease (Fadini et al, ), coronary artery disease (Briguori et al, ), congestive heart failure (Valgimigli et al, ), lowering cholesterol (Vasa et al, ), anti‐diabetic medication (Wang et al, ), and early revascularization of ovaries (Cha et al, ). Although EPCs do not engraft into the vasculature, it is now considered that the primary role of the contribution to vascular functions by circulating EPCs is via the release of paracrine factors including VEGF, bFGF, and IL‐10 (Jujo, Ii, & Losordo, ; Yang, Wang, Qu, Duan, & Xu, ; Zhang, Malik, & Rehman, ).…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, it has been increasingly common to transplant ovarian tissue installed in acellular scaffolds of materials such as fibrin [11][12][13], alginate [14], Matrigel [15], and collagen [16]. However, there is still no consensus on the ideal material.…”
Section: Introductionmentioning
confidence: 99%
“…This is because ovarian tissue transplantation is conducted without the initial anastomosis of blood vessels [22]. In the present study, the ovarian tissues were transplanted under the kidney capsule without anastomosis of the blood vessels during the early transplantation period (pre-angiogenesis).…”
Section: Discussionmentioning
confidence: 99%
“…In 2 h of in vitro culture group, there were no significant differences in primary follicles. Regarding the intact (G1) secondary follicles after 24 h of in vitro culture, the ratio of the 1000 U/ml PEG-SOD treatment group (45 %) was significantly greater than those of the other 24-h culture groups (25,22, and 25 % in 0, 10, and 100 U/ml groups, respectively) ( Table 1). In terms of antral follicles, 2 h-0 U/ml group (51 %) and 12 h-0 U/ml group (33 %) had showed the significantly higher intact (G1) antral follicle ratio compared with 2 h-10 U/ml (40 %) group and 12 h-100 U/ml (19 %) group.…”
Section: Ovarian Follicle Integritymentioning
confidence: 97%